Pengembangan E-LKPD Berbasis Etnomatematika Alat Tangkap Ikan Berupa Bubu pada Materi Bangun Ruang Kelas VIII SMP - Manurung, Julian Lois; Febrian, Febrian; Astuti, Puji (Jurnal Gantang, 2024)
This study aims to produce an e-worksheet product based on ethnomathematics of fish trap in the form of Bubu on valid and practical space geometry material. This type of research is Research and Development (R&D) using the ADDIE development model. According to the needs of the researchers in this study, they only carried out three stages: analysis, design, and development. The data collection instruments were expert validation sheets and teacher and student response questionnaires. The data obtained were qualitative and then converted into quantitative data on an interval scale using MSR. The results of the material expert validation obtained an assessment of 80.36% with very valid criteria, the media expert validation obtained an assessment of 82.51% with very valid criteria, and the language expert validation obtained an assessment of 82.27% with very valid criteria. The results of the practicality test by the teacher obtained an assessment of 81.09% with very practical criteria, and the practicality test by students obtained an assessment of 84.33% with very practical criteria. The ethnomathematics-based e-worksheet that was developed has achieved valid and practical criteria. Therefore, the product created is worthy of being tested for its effectiveness.